Technology convergence: the evolving mobile phone - Vatanparast, Ramin (Henry Stewart Talks, 2009)
Forecast, Trends, Mobility and convergence, Mobile device trends, Mobile phones connectivity, Mobile service trends, Mobile marketing, Convergence challenges
Archived at 2022/04/11